PENGARUH PEMANFAATAN MEDIA AUDIO VISUAL TERHADAP MOTIVASI DAN HASIL BELAJAR PKN SISWA KELAS IV SDN BONTORAMBA - Ashari; Abdul Azis; Musdalifah Syahrir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the use of audio-visual media on the motivation and learning outcomes of civic education of grade IV students of SDN Bontoramba. This study uses a quantitative research type with an experimental approach with a quasi-experimental design or pseudo-experiment. The design used in this study is a quasi-experimental type of Nonequivalent Control Group Design. The research instruments used for data collection are observation, questionnaire sheets, learning outcome tests including pre-test and post-test and documentation. The data analysis techniques used include the first stage, namely data processing consisting of data classification, editing, coding, scoring and tabulation. The second stage is data analysis consisting of Normality Test, Homogeneity Test, Hypothesis Test, T-test and the third Manova Test. The results of the study showed that the use of audio-visual media significantly increased students' learning motivation. The average learning motivation of students in the experimental class was 86.64 while in the control class it was 78.09. In addition, student learning outcomes also increased. The average post-test learning outcomes in the experimental class were 86.29, while in the control class it was 75.80. The results of the study showed that the use of audio-visual media significantly increased students' motivation and learning outcomes compared to conventional methods. The learning motivation of students involved in this interactive learning process has a direct positive impact on their learning outcomes. Thus, audio-visual media is effectively applied in Civic Education learning to improve learning outcomes. The results of hypothesis testing using the Independent Sample Test showed a t-test of 0.034, meaning that the value is smaller than the significance level of 0.05 or 0.034 <0.05. Therefore, Ho is rejected and H1 is accepted, which means that the use of audio-visual media has a significant effect on students' motivation and learning outcomes compared to conventional learning methods in the control class.